Effects of changing speed on knee and ankle joint load during walking and running - de David, A. C.; Carpes, F. P.; Stefanyshyn, D. (Journal of Sports Sciences, 2015)
Joint moments can be used as an indicator of joint loading and have potential application for sports performance and injury prevention. The effects of changing walking and running speeds on joint moments for the different planes of motion still are debatable. Here, we compared knee and ankle moments during walking and running at different speeds. Data were collected from 11 recreational male runners to determine knee and ankle joint moments during different conditions. Conditions include walking at a comfortable speed (self-selected pacing), fast walking (fastest speed possible), slow running (speed corresponding to 30% slower than running) and running (at 4 m/s ± 10%). A different joint moment pattern was observed between walking and running. We observed a general increase in joint load for sagittal and frontal planes as speed increased, while the effects of speed were not clear in the transverse plane moments. Although differences tend to be more pronounced when gait changed from walking to running, the peak moments, in general, increased when speed increased from comfortable walking to fast walking and from slow running to running mainly in the sagittal and frontal planes. Knee flexion moment was higher in walking than in running due to larger knee extension. Results suggest caution when recommending walking over running in an attempt to reduce knee joint loading. The different effects of speed increments during walking and running should be considered with regard to the prevention of injuries and for rehabilitation purposes.